Effect of sanitizing agents on the microbiological quality of minimally processed cabbage strips - Custodio, Cristina Elisa Mayor; Acevedo, Teresita P. (2000., 2000)
ABSTRACT The effect of sanitizing agents on the microbiological quality of minimally processed cabbage strips was determined in this study. The cabbage strips were immersed in a 200-ppm chlorine solution for 10 minutes. A commercially prepared sanitizing agent was also utilized and the cabbage strips were likewise soaked in this solution for 5 minutes. Samples were taken before and immediately after each treatment and were subjected to the determination of aerobic mesophilic count, lactic acid bacterial count, coliform count, and Escherichia coli. The results from the microbiological tests were compared and the more effective sanitizing agent was chosen based on the log reduction effect. The selected sanitizing agent was then used in the production of minimally processed cabbage strips. Microbiological analyses were done on samples collected from each processing step in order to determine which step/s greatly contribute to the microbial count of the product. Chlorine treatment resulted in a 0.4 log unit decrease in aerobic count while the commercially prepared sanitizing agent reduced the number of aerobic mesophiles by a 0.3 log unit. These results suggest that chlorine is more effective in reducing the number of aerobic mesophiles. Lactic acid bacterial (LAB) count decreased by 2.0 log units after chlorine treatment. After treating the cabbage strips with the commercially prepared sanitizing agent, LAB count increased by 0.2 log unit. Log reduction showed that chlorine decreased the number of coliforms to lower levels as compared to the commercial sanitizing agent. The 200 ppm chlorine solution was chosen to be more effective than the commercial sanitizing agent and was utilized inthe production of minimally processed cabbage strips. Aerobic mesophilic count increased by a 0.9 log unit after removing outer cabbage leaves, by a 0.2 log unit after the leaves were cut into strips and by a 0.3 log unit after packing the cabbage strips. E. coli was not detected in all of the samples. The presence of coliforms was probably due to Enterobacter aerogenes, the Citrobacter and the Klebsiella genera. The organisms have been found to be abundant in soils and plant materials(Jay, 1986). It was shown that both sanitizing agents reduced the number of spoilage and coliform bacteria. While the sanitizing agents are capable of decreasing microbial counts, their effect on the nutritional components of food should also be studied. The nature and mounts of disinfection-by-products (DBPs) should also be studied in order to determine the safety of sanitizing agents.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Cabbage; Vegetables -- Preservation